Design process innovation through flexible and circular technological solutions - Antonella Violano; Monica Cannaviello (Vitruvio: International Journal of Architectural Technology and Sustainability)
The goal of optimizing material resources and the polyvalent use of space lead to the development of new technologies within a renewed architectural spatiality, which from the point of view of effectiveness of choices allow for low-carbon buildings. The climate emergency, in fact, asks us today to reinterpret Vitruvius’ concept of Firmitas according to the criteria of durability reliability and resilience associated with widespread usability functionality and circularity (Utilitas) traceable throughout the life cycle a building. The paper illustrates the results of a scientific research project that led to the construction of a prototype of a “minimal” residence, designed and built with the “total low” approach, characterized by regenerative design, economy, lightness, ease of assembly, recyclability, as well as excellent overall performance and high levels of comfort. The idea of a building, easily assembled and disassembled, is a strength of the “Petite-Cabane” design concept: a 3x3 m single-user minimum residential unit made with the Light Gauge Steel Building System (LGS) produced with controlled automatically roll forming machine, for which high technological and energy performance envelope packages. The design of a small house becomes the “mise en forme” of a space in which “essential” equipment, energy performance, architectural qualities, economic and environmental costs are linked to the ease and immediacy of construction but also to the flexibility and circularity of technological choices.